PENGHULU WANITA DALAM PERSEPEKTIF FIQIH DAN UNDANG- UNDANG - Imam Fauzan (Jurnal Penelitian Ilmiah INTAJ, 2022)
Although many women occupy strategic positions, both in the legislative, executive, and social life, in the realm of penghulu in Indonesia, there has never been found a woman who has become a structural position in KUA or becomes a penghulu. These positions are still assumed to be the domain of men. By using a normative approach, this study focuses on the problem of how female leaders are from the perspective of fiqh and law. The appointment of women as penghulu was not carried out due to two reasons, namely juridical-normative and sociological-psychological. juridically-normatively Article 3 Regulation of the Minister of Religion No. 30 of 2005 concerning Guardian Judges which states that guardian judges are the Head of the District KUA, Penghulu, and Penghulu Assistant. In other words, if women are appointed as Penghulu, their position will be questioned if they carry out their duties as guardian judges which in fiqh must be a man.